2021
DOI: 10.3389/fphys.2021.659977
|View full text |Cite
|
Sign up to set email alerts
|

Biological Functions of RBP4 and Its Relevance for Human Diseases

Abstract: Retinol binding protein 4 (RBP4) is a member of the lipocalin family and the major transport protein of the hydrophobic molecule retinol, also known as vitamin A, in the circulation. Expression of RBP4 is highest in the liver, where most of the body’s vitamin A reserves are stored as retinyl esters. For the mobilization of vitamin A from the liver, retinyl esters are hydrolyzed to retinol, which then binds to RBP4 in the hepatocyte. After associating with transthyretin (TTR), the retinol/RBP4/TTR complex is re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 175 publications
1
103
0
4
Order By: Relevance
“…We further focused on the DEGs in this group of genes and applied PPI network analysis to distinguish hub genes, which are defined as genes with a high degree of connectivity that play an essential role in stabilizing the PPI network structure. Here, some star genes were identified, such as RBP4 20 , SPP2 21 and MAPK3 22 , those had been confirmed a role in pathological mechanisms. Fourth, DEGs specific to CCA subtypes were explored and compared.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We further focused on the DEGs in this group of genes and applied PPI network analysis to distinguish hub genes, which are defined as genes with a high degree of connectivity that play an essential role in stabilizing the PPI network structure. Here, some star genes were identified, such as RBP4 20 , SPP2 21 and MAPK3 22 , those had been confirmed a role in pathological mechanisms. Fourth, DEGs specific to CCA subtypes were explored and compared.…”
Section: Discussionmentioning
confidence: 57%
“…Out of this module, 579 DEGs were extracted and hub genes were identified through PPI network analysis. The PPI network suggested that RBP4 20 , SPP2 21 , MAPK3 22 and another around 30 genes were hub genes (Fig. 3 d).…”
Section: Resultsmentioning
confidence: 97%
“…Although the involvement of TTR in the transport of thyroid hormones [ 37 ] and retinol through binding to RBP [ 38 ], as well as in the development of familial amyloidotic polyneuropathy (FAP) [ 39 ], is well established, its other roles, such as neuroprotective and metabolic roles, began to be explored only recently.…”
Section: Discussionmentioning
confidence: 99%
“…RBP4 was identified in the 1960s by Kanai et al as the plasma transporter of retinol complexed with transthyretin (TTR). This 21 kDa lipocalin is mainly expressed in liver and adipose tissue, and various other tissues at lower levels, and is the main—if not the only—transporter of vitamin A in vivo [ 8 ]. Some gain-of-function mutations on RBP4 promoter were reported to be associated with a higher risk of developing obesity or type 2 diabetes [ 15 , 16 ] while a non-coding mutation in RBP4 promoter is associated with dyslipidemia [ 17 ].…”
Section: Rbp4mentioning
confidence: 99%